ITD Data Quality Maturity (A Case Study) (International Journal of Engineering and Computer Science, 2019)
Nowadays, more and more organizations are realizing of importance of their data, because it can be considered as an important asset in present nearly all business organizational processes. Information Technology Division (ITD) is a department in the International Islamic University Malaysia (IIUM) that consolidates efforts in providing IT services to the university.The university data management started with decentralized units, where each center or division has its own hardware and database system. Later it improved to become became centralized, and ITD is now trying to one policy across the whole university. This will optimize the high performance of data management in the university. A visit has been done to ITD building and a presentation has been conducted discussing many issues concerning data management quality maturity in IT division at IIUM. We got some notices like server’s room location, power supply and backup and existence of data redundant. These issues are discussed in details in the next sections of this paper and some recommendations are suggested to improve data quality in the university.The quality of the data is very important in decision making, especially for a university that is trying to improve its strategy towards a research university and rise its rank among the World University Ranking.